The Dispossessed State Narratives of Ownership in Nineteenth-Century Britain and Ireland - Maurer, Sara L. (Johns Hopkins University Press, 2012)
Do indigenous peoples have an unassailable right to the land they have worked and lived on, or are those rights conferred and protected only when a powerful political authority exists? In the tradition of John Locke and Thomas Hobbes, who vigorously debated the thorny concept of property rights, Sara L. Maurer here looks at the question as it applied to British ideas about Irish nationalism in the nineteenth century. This book connects the Victorian novel's preoccupation with the landed estate to nineteenth-century debates about property, specifically as it played out in the English occupation of Ireland. Victorian writers were interested in the question of whether the Irish had rights to their land that could neither be bestowed nor taken away by England. In analyzing how these ideas were represented through a century of British and Irish fiction, journalism, and political theory, Maurer recovers the broad influence of Irish culture on the rest of the British Isles.By focusing on the ownership of land, The Dispossessed State challenges current scholarly tendencies to talk about Victorian property solely as a commodity. Maurer brings together canonical British novelists-Maria Edgeworth, Anthony Trollope, George Moore, and George Meredith-with the writings of major British political theorists-John Stuart Mill, Henry Sumner Maine, and William Gladstone-to illustrate Ireland's central role in the literary imagination of Britain in the nineteenth century.The book addresses three key questions in Victorian studies-property, the state, and national identity-and will interest scholars of the period as well as those in Irish studies, postcolonial theory, and gender studies.